Contribution in removal water hardness by soda ash which formed from hearth firewood (Latakia University Journal -Basic Sciences Series, 2018)
This study aims to use the ash formed from the burning of firewood and the different pruning residues to remove the hardness of waterSoda ash was characterized using different techniques, including XRD,flame spectroscopy , volume titration and others.These methods aim to determine the composition of the ash and the components which are contributing to the removal process.The optimum mixing time was determined using certain amount of soda ash to the hard water and the water hardness was determined in the rang of time (0.5, 1, 2, 3, 4 and 5h) where the ideal time was 3 hours.The removal ratios were determined when the mixing time of the two phases was 3 h, and adding directly the following quantities of ash (0.5,1,2,3,5,7,10,15,20,25) g to 200 ml of highly hardened water. The removal rate was increased by increasing the amount of added ash. The removal rate was approximately 50% when 1 g of ash was used and the complete removal rate of 100% was achieved when the amount of ash was 25 gز***llah Muhammad Primozli .* hearth firewood بازدياد كمية الرماد  كميات التالية من الرماد ( .